Early experience with Telehealth during sport activities - Migliau, G; Bertazzoni, G; De Castro, S; Pantani, E; Tassoni, G (Cor et vasa, 1987)
In order to verify the usefulness of a system designed to provide participants of sport competitions with a cardiological emergency service, the authors utilized a cardiotelephone apparatus during a "24-hour Marathon race" in which 1008 subjects took part. In 18 cases, an ECG was transmitted owing to various symptoms after exertion. One case of pseudoischaemia and one of complete A-V block were registered. The authors emphasize the importance of a telephone ECG transmission system as a special aid able to cut down the intervention time without moving the patients.
Keywords: dospělí; Physical Exertion; Telephone; modemy; bolesti na hrudi; Adult; sporty; únava; Adolescent; Modems; běh; lidé; Fatigue; telefon; Electrocardiography; elektrokardiografie; Running; Chest Pain; Sports; tělesná námaha; lidé středního věku; Middle Aged; mladiství; Humans